2020
DOI: 10.2147/cmar.s262442
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-105 Promotes the Progression and Predicts the Prognosis for Oral Squamous Cell Carcinoma (OSCC)</p>

Abstract: Background miRNA-105 has been reported in a vast number of malignancies, including hepatocellular carcinoma and colorectal, esophageal, breast and non-small lung cancers. Still, the biological role of miR-105 remains mostly uncovered in oral squamous cell carcinoma (OSCC). Methods miR-105 expression in OSCC tissues and cell lines was detected by qRT-PCR. Survival analysis was performed using the Kaplan–Meier method, while the prognostic significance of miR-105 was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These data indicated that PRKAG2-AS1 and SRRM2-AS1 might play roles in the recurrence prognosis of COAD by regulating their corresponding target miRNAs. Except for miR-6514 and miR-3130, accumulating evidence has revealed the functional roles of miR-1275 [ 46 , 47 ] and miR-105 [ 48 , 49 ] in the development of tumorigenesis. The function enrichment analysis identified the PPAR_SIGNALING_PATHWAY and CYTOKINE_CYTOKINE_RECEPTOR_INTERACTION significantly associated with PRKAG2-AS1 and SRRM2-AS1, which might be the recurrence prognosis of COAD.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that PRKAG2-AS1 and SRRM2-AS1 might play roles in the recurrence prognosis of COAD by regulating their corresponding target miRNAs. Except for miR-6514 and miR-3130, accumulating evidence has revealed the functional roles of miR-1275 [ 46 , 47 ] and miR-105 [ 48 , 49 ] in the development of tumorigenesis. The function enrichment analysis identified the PPAR_SIGNALING_PATHWAY and CYTOKINE_CYTOKINE_RECEPTOR_INTERACTION significantly associated with PRKAG2-AS1 and SRRM2-AS1, which might be the recurrence prognosis of COAD.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are considered as master regulators of molecular pathways in cancers (Refs 4449). MiRNA dysregulation is an obvious finding in cancer, and these short ncRNAs are reliable biomarkers for cancer detection and prognosis (Refs 50, 51). For instance, in breast cancer patients, miRNA-221 and miRNA-489 demonstrate upregulation and down-regulation in expression, respectively.…”
Section: Micrornas In Oncology: An Overviewmentioning
confidence: 99%
“…Altered levels of miRNA expression are highlighted in several neoplastic diseases including cervical [ 18 ], colon [ 19 ], lung [ 20 ], ovarian [ 21 ], and breast cancers [ 22 ]. Recent studies [ 23 , 24 , 25 ] have reported that oral cancers are not an exception to this rule but altered levels of miRNAs can lead to carcinogenesis ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 98%
“…Altered levels of miRNA expression are highlighted in several neoplastic diseases including cervical [18], colon [19], lung [20], ovarian [21], and breast cancers [22]. Recent studies [23][24][25] have reported that oral cancers are not an exception to this rule but altered levels of miRNAs can lead to carcinogenesis (Figure 1). The purpose of this review is to highlight the essential roles of miRNA dysregulation in oral cancer development and progression, presenting the most relevant transcripts with either tumor suppressor or oncogenic roles.…”
Section: Introductionmentioning
confidence: 99%